(untitled) (Journal of Ideas in Health, 2024)
Background: Inflammatory demyelinating diseases of the central nervous system (CNS) are autoimmune conditions leading to significant neurological disability in adults. Recent classifications include myelin oligodendrocyte glycoprotein antibody associated disease (MOGAD) and neuromyelitis optica spectrum disorder (NMOSD) which pose diagnostic challenges due to overlapping clinical and radiological features. This study aimed to assess the clinical spectrum among adults and children diagnosed with CNS demyelinating diseases and to find the proportion of MOG and/or aquaporin-4 (AQP4) autoantibodies amongst them. Methods: This single-center, retrospective study examined 20 patients diagnosed with CNS demyelinating disorders between March, 2023 and February, 2024. Data pertaining to demographics, disease types, CSF analysis, MRI findings, treatment modalities, and serological profiles for anti-AQP4 and anti-MOG antibodies were collected from hospital records and evaluated. Results: Among 20 patients [median age, 34 years (IQR, 18.75); males (n=10) and females (n=10)], acute transverse myelitis (TM) was the most common demyelinating disorder at onset (60%) followed by optic neuritis (ON) (20%). CSF analysis found elevated protein levels in 53% and pleocytosis in 33% of patients. MRI findings revealed longitudinal extensive involvement in 52% of patients, predominantly affecting the cervical and dorsal spine. Serological testing identified 15% positive for anti-AQP4 and 10% for anti-MOG antibodies. MOG+ patients were significantly younger than AQP4+ patients (mean age 16.5 vs. 36.66 years, p=0.016). Both MOG+ patients were male, with 50% presenting with acute TM and 50% with acute disseminated encephalomyelitis. Among AQP4+ patients, the male-to-female ratio was 1:2, with 66.66% presenting with acute TM and 33.33% with ON. Conclusion: CNS demyelinating disorders primarily affect younger individuals, with TM as the most common initial disorder and extensive spinal involvement in cervical and dorsal regions. Serological testing identified three patients with anti-AQP4 and two with anti-MOG antibodies, providing valuable insights into the clinical spectrum of these disorders through cell-based assays.